Penerapan Media Audio Visual dalam Mengembangkan Kemampuan Membaca Anak Slow Learner di Mi Darul Akhlak Pamekasan Madura - Ulfah, Septiana; Sa’diyah, Halimatus (Arden Jaya Publisher, 2024)
The study aims to improve the reading ability of slow learner children through audio-visual media. Audio-visual media this was tried to be applied to slow learner children to see how far the effectiveness of audio visual media is to improve slow learner children’s reading skills. This media is used for slow learner children with the initials S who attend MI Darul Akhlak. This reseach was conducted for 16 days with 8 meetings held every 2 days. By using qualititative research methods that are descriptive. With data collection tecniques through interviews and observation. From this study, it shows that the application of audio-visual media can improve the reading ability of slow learner children at MI Darul Akhlak. Because by using this audio-visual media students better understand the material provided by researchers and students tend not to get bored quickly and are attracted to learning.